Genetic analysis of resistance to Fusarium wilt disease, yield and yield-related traits of pigeonpea (Cajanus Cajan (L.) Millsp.) - Didas Kimaro; Rob Melis; Julia Sibiya; Hussein Shimelis (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2020)
Understanding the genetic control of Fusarium wilt resistance is crucial in pigeonpea breeding programme. This study aimed to study the gene action controlling Fusarium wilt resistance, yield and yield components and select promising crosses possessing resistance to Fusarium wilt along with important agronomic yield traits. Six lines were crossed with four testers in a line x tester mating design. For Fusarium wilt reaction, F1’s progenies were evaluated in a sick field having inoculums of Fusarium wilt at one location for two seasons and in a pot as well. The F1’s and parents were evaluated for yield and yield components at two locations for two seasons using a row-column design with two replications. Results indicated that parents and crosses had highly significantly difference for yield and important agronomic traits. General combining ability (GCA) effects of lines and testers were also significant. Specific combining ability (SCA) was also significant for some crosses. Non-additive gene action was more important than additive gene action except for days to maturity and plant height. Crosses ICEAP 00932 × TZA 2439 and ICEAP 00932 × TZA 197 displayed small effects of SCA for Fusarium wilt and large SCA for most of yield traits and should be used for integrated disease management.